RALDE: Re-thinking Active Learning for Distance Education - Herrero, Ó.; Azqueta, A. (Spanish Journal of Environmental Mutagenesis and Genomics, 2025)
The COVID-19 pandemic challenged higher education institutions (HEIs) to rapidly transition from traditional face-to-face teaching to fully online formats, often without adequate tools or digital pedagogy training. The Erasmus+ RALDE project (2020-1-FR01-KA226-HE-095581; https://main-site.ralde.eu) responded to these challenges by developing innovative and accessible digital teaching resources aimed at Biology and Environmental Sciences in HE. The main goal was to enhance digital education quality, promote active learning methodologies, and support educators and students in acquiring relevant digital competencies. RALDE adopted a multipronged strategy that included: (i) a European survey to assess pedagogical responses during the pandemic; (ii) the design of virtual practicals—such as a rodent necropsy and a cell culture lab simulation; (iii) the development of problem-based learning (PBL) modules; and (iv) gamified tools, including a serious game on cell culture techniques. Additionally, the project produced Do It Yourself tutorials to empower teachers to create their own digital content, and a dedicated module to improve scientific communication skills among MSc and PhD students. These outputs are freely accessible through the RALDE platform, including a podcast series and video materials hosted on YouTube. Overall, the project generated more than 150 hours of online teaching content and provided practical training for educators and learners. RALDE demonstrates how targeted, high-quality digital tools can not only bridge the gap left by traditional methods during crises, but also permanently enrich teaching practices by fostering engagement, autonomy, and collaborative learning. Acknowledgements: The authors acknowledge the contributions of all RALDE partners. Funding: Funded by Erasmus+ KA226 - Partnerships for Digital Education Readiness.